2002
DOI: 10.1001/archpedi.156.9.893
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Failure

Abstract: Acute kidney failure following repair of cardiac lesions remains unchanged as a leading risk factor of mortality in both decades. Three organ system failures were associated with more than a 50% mortality rate. Predialysis low serum albumin concentrations emerged as a significant copredictor of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(40 citation statements)
references
References 34 publications
2
35
2
Order By: Relevance
“…A number of studies in critically ill children have demonstrated an association of clinical severity-evaluated using the PRISM, PIM, and PELOD scores-and the number of organ failures at the start of CRRT and mortality rates [5,7,8,11,16]. However, none of these studies analyzed the This only applies to patients who survived SD standard deviation, MAP mean arterial pressure, PRISM Pediatric Risk of Mortality score, PIM Pediatric Index of Mortality score, PELOD Pediatric Logistic Organ Dysfunction relationship of these factors with CRRT duration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of studies in critically ill children have demonstrated an association of clinical severity-evaluated using the PRISM, PIM, and PELOD scores-and the number of organ failures at the start of CRRT and mortality rates [5,7,8,11,16]. However, none of these studies analyzed the This only applies to patients who survived SD standard deviation, MAP mean arterial pressure, PRISM Pediatric Risk of Mortality score, PIM Pediatric Index of Mortality score, PELOD Pediatric Logistic Organ Dysfunction relationship of these factors with CRRT duration.…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with a higher mortality rate are clinical severity, underlying disease, and-above all-the hemodynamic status at the start of therapy [4][5][6][7][8][9][10][11]. Some studies have found a higher mortality rate among children with heart disease than among other patients requiring CRRT, particularly in those undergoing cardiac surgery [5,8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While multicenter data do not exist, single center studies from the 1980s and 1990s report hemolytic uremic syndrome (HUS), other primary renal causes, sepsis, and burns as the most prevalent causes leading to pAKI [6,7]. More recent pediatric data [4,8,9,10] reveal a dramatic shift in the epidemiology of pAKI (table 1), with the most common causes being renal ischemia (often after cardiopulmonary bypass surgery [10]), nephrotoxin use, and sepsis; thus, pAKI more often develops in hospitalized children as a result of another systemic illness or its treatment and not from primary kidney disease. pAKI epidemiological study has intensified over recent years, likely as a result of more widespread provision of acute RRT modalities to critically ill children [11].…”
Section: Epidemiology Of Pediatric Akimentioning
confidence: 99%